Production and operations management - Garg, Ajay K (Tata McGraw Hill Education Pvt. Ltd., 2012)
Production and operations management / Garg, Ajay K. -- New Delhi: Tata McGraw Hill Education Pvt. Ltd., 2012 658.5 G232 No. of Copies : 1